EVALUASI KANDUNGAN PROTEIN DAN SIFAT PASTA BERAS JAPONICA DENGAN MARKA DNA - Lestari, Puji; Koh, Hee Jong (Research Center for Biology-Indonesian Institute of Sciences, 2013)
An evaluation of protein content and pasting properties of rice using molecular markers approach is still limited. This study was aimed to evaluate protein content and pasting properties of japonica rice using DNA marker in complement to conventional tools. This study was further analysis based on the data of protein content and pasting properties of 22 japonica varieties and genotyping data using 30 DNA markers. Multiple regression analysis was performed to formulate equations to estimate the protein content and pasting properties. As a result, the protein content and Rapid Visco Analyzer (RVA) pasting properties values of 22 varieties demonstrated in the range of japonica rice with high variation. Correlation between protein content and RVA pasta properties showed differential profiles. Several type of DNA markers tested in this study showed allele variation among varieties. To estimate the protein content and several parameters of pasting properties of japonica rice, six marker sets in the form of model equations were successfully developed. High resolutions of equations with signifikant R2 in range of 0.95 - 0.99 showed their potency to predict rice physicochemical properties. These developed marker sets are an initial step which needs further validation in order to be able for evaluation of thephysicochemical properties in early generation of breeding and germplasm collection of japonica rice in the future.